Where is it and How Does it Get There – Intracellular Localization and Traffic of P-glycoprotein - Fu, Dong (Frontiers in Oncology, 2013)
P-glycoprotein (P-gp), an ATP-binding cassette (ABC), is able to transport structurally and chemically unrelated substrates. Overexpression of P-gp in cancer cells significantly decreases the intercellular amount of anticancer drugs, and results in multidrug resistance in cancer cells, a major obstacle in cancer chemotherapy. P-gp is mainly localized on the plasma membrane and functions as a drug efflux pump; however, P-gp is also localized in many intracellular compartments, such as endoplasmic reticulum, Golgi, endosomes and lysosomes. P-gp moves between the intracellular compartments and the plasma membrane in a microtubule-actin dependent manner. This review highlights our current understanding of 1) the intracellular localization of P-gp; 2) the trafficking and cycling pathways among the cellular compartments as well as between these compartments and the plasma membrane; and 3) the cellular factors regulating P-gp traffic and cycling. This review also presents a potential implication in overcoming P-gp-mediated multidrug resistance by targeting P-gp traffic and cycling pathways and impairing P-gp localization on the plasma membrane.